From Crude to Clarity: Rethinking Oil Price Predictions - Rudling,Tom; Hansell,Axel (2025)
Oil price forecasting is critical for financial markets, economic and geopolitical stability, and has a direct impact on the energy transition. Therefore, practitioners in the financial industry strive to understand the key drivers of the oil price and determine its best prediction model. This thesis investigates whether the exchange rates of oil-importing countries have predictive power in explaining oil prices. To explore this relationship, we perform the Granger causality test on a dataset containing daily observations on the Japanese yen, South Korean won, and Brent crude oil price. The results indicate that the Japanese yen to USD and the South Korean won to USD exchange rates jointly possess some predictive power for the Brent oil price. Our findings are more pronounced when denoting the exchange rates in GBP. Additionally, the results are robust when firstly adjusting for Newey-West standard errors and secondly, accounting for parameter instabilities. Our findings inform financial sector practitioners and academics that exchange rates of oil-importing countries should also be considered when modeling oil price forecasts.
Keywords: Granger Causality; Vector Autoregression; Present Value Model; Japanese Yen; South Korean Won